Updating the NlOSH Support Technology Optimization Program (STOP) With New Support Technologies and Additional Design Features - Thomas M. Barczak (International Conference on Ground Control in Mining, 2001)
The initial Support Technology Optimization Program (STOP), Version 1.0, was released at the 19th Gmund Control Conference. This original program has since been updated to Version 2.3 which was released in May, 2001. This paper describes the additional features of Version 2.3, focusing primarily on the following three aspects: (I) including uncontrolled convergence into the design requirements for standing roof supports, (21 the addition of design procedures for cable bolts as an alternative secondary roof support, and (3) the addition of new standing roof support technologies. Another new feature which should facilitate the development of design criteria for standing roof support is the capabilily to define ground reaction curves through convergence measurements alone wthout having to make support loading measurements. There are several other new features provided in Version 2.3 which are only briefly addressed in the paper. These include: (I) additional graphics capabilities to facilitate rapid assessment of support comparisons. (2) an East-West designation for support selection to more accurately provide cost and support availability data, (3) additional safety measures including a safety factor to identify support design near the peak support capacity, checks to see if the support dimensions comply with aspect ratio requirements, and measure of roof coverage for the design layout of the support system These new features of STOP provide more capabilities to design and analyze secondary roof support systems for conditions whlch could not be fully analyzed in the original version of the program.